KONSEP KEAGAMAAN MUHAMMADIYAH DALAM ISLAM BERKEMAJUAN: TINJAUAN MANHAJ TAJDID , TARJIH DAN PENDIDIKAN MUHAMMADIYAH - Hasnahwati, Hasnahwati; Romelah, Romelah; Hakim, Moh. Nur (Jurnal Panrita, 2022)
The existence of Muhammadiyah as a modern Islamic organization and carrying out Islamic da'wah rahmatan lil alamin and carrying out progressive Islam, as well as the amar ma'ruf and nahi munkar movements. Muhammadiyah also carries out its Islamic vision with inclusive moderate Islam. Indonesia, with a diverse population that has unique personal characteristics, makes Muhammadiyah a moderate form of Islam that can mingle with various other religions in Indonesia. This research is a library research and the nature of this research is descriptive-analytical related to the religious concept of Muhammadiyah. The step method used in collecting data is to find and collect reference sources through books, journals and websites related to the author's research title. Muhammadiyah uses two strategies to spread progressive Islam: namely the enlightenment strategy and the transformational strategy. Enlightenment strategies try to reach people with advanced Islamic ideas through education and transformation strategies try to change people's way of thinking through preaching and activism. Tajdid has two meanings, namely: 1) In the field of faith and worship, 2) Tajdid muamalatduniayah. The position of Tarjih is at a low level of Ijtihad, based on the level of Ijtihad which includes 4 types, namely: a) absolute ijtihad in clauses and branches; b) ijtihad at the branch; c) ijtihad on sects; d) Ijtihad in Tarjih. the concept of progressive education is a reflection of holistic Islamic education that enlightens.